1999
DOI: 10.1016/s0092-8674(00)80735-7
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Arrestin’s Regulation: The 2.8 Å Crystal Structure of Visual Arrestin

Abstract: G protein-coupled signaling is utilized by a wide variety of eukaryotes for communicating information from the extracellular environment. Signal termination is achieved by the action of the arrestins, which bind to activated, phosphorylated G protein-coupled receptors. We describe here crystallographic studies of visual arrestin in its basal conformation. The salient features of the structure are a bipartite molecule with an unusual polar core. This core is stabilized in part by an extended carboxy-terminal ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
390
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 395 publications
(418 citation statements)
references
References 59 publications
(4 reference statements)
11
390
1
Order By: Relevance
“…Arrestin/Receptor Interaction and Receptor Internalization-The current model for the understanding of arrestin interaction with the receptor is based on rhodopsin studies and the recent crystal structures of visual arrestin and ␤-arrestin (12,13,43). The model proposes that an initial binding of arrestin to the phosphorylated residues in the carboxyl tail of the receptor disrupt intramolecular charge-charge interactions between highly basic residues in arrestin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arrestin/Receptor Interaction and Receptor Internalization-The current model for the understanding of arrestin interaction with the receptor is based on rhodopsin studies and the recent crystal structures of visual arrestin and ␤-arrestin (12,13,43). The model proposes that an initial binding of arrestin to the phosphorylated residues in the carboxyl tail of the receptor disrupt intramolecular charge-charge interactions between highly basic residues in arrestin.…”
Section: Discussionmentioning
confidence: 99%
“…The current model for the understanding of the arrestinreceptor interaction mechanism is based on various studies of visual arrestin interaction with rhodopsin (11)(12)(13)(14)(15)(16). Visual arrestin binding with rhodopsin requires GRK-1 phosphorylated residues, and the contact of phosphorylated residues with a cationic region of arrestin switches it into an active conformation, enabling interaction with an exposed binding site on activated rhodopsin.…”
Section: Agonist Binding To Most G Protein-coupled Receptorsmentioning
confidence: 99%
“…Early structural studies conducted on ␤-arr1 and arrestin, found exclusively in visual tissues, reported the existence of oligomers in crystals, indicating that this family of proteins may have the propensity to form oligomers (13)(14)(15). However, the existence of constitutive oligomers in living cells at physiological concentrations was only recently confirmed (16).…”
mentioning
confidence: 99%
“…Mechanisms for the binding of arrestins to receptors have been described based largely on biochemical, biophysical, structural, and mutational studies of visual arrestin (8). This protein exhibits great selectivity for binding to light-activated, phosphorylated rhodopsin, with binding resulting in signal termination (9).…”
mentioning
confidence: 99%
“…This protein exhibits great selectivity for binding to light-activated, phosphorylated rhodopsin, with binding resulting in signal termination (9). With the recent x-ray crystallographic determination of visual arrestin, a much more precise understanding of the functional properties of arrestins has come to light (8). The structure of visual arrestin consists of two domains with a highly polar core comprised mostly of amino-terminal domain residues.…”
mentioning
confidence: 99%